Psychometric evaluation of diagnostic test instruments on physics wave material - AM, Muh. Asriadi; Sanam, Anna Isabela (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2025)
This study aims to evaluate the psychometric quality of diagnostic test instruments on wave material in physics learning, with a focus on their validity and reliability. The instrument was validated by seven experts using the content validation method, which resulted in an average validity score of 0.849, indicating that the instrument is very valid. Confirmatory factor analysis (CFA) was conducted to test the model fit and validity of the instrument structure. The KMO test results showed a figure of 0.946, indicating the suitability of the data for factor analysis, while the Bartlett Test of Sphericity results confirmed that the intercorrelation data was not an identity matrix. The tested model showed a good fit to the data, with a CFI value of 0.948, TLI of 0.935, and RMSEA of 0.072. The model parameter estimates showed a significant relationship between the latent variables and the observed items, with a strong influence from the